The influence of spatial distance and environment on small-scale genetic variability in eelgrass and its application for restoration - Ries, Stefanie; Jahnke, Marlene; Enge, Swantje; Pansch, Christian; Hattich, Giannina S I; Bernal-Gómez, Maru; De Wit, Pierre; Havenhand, Jonathan N (University of Gothenburg, 2025)
This item includes data files and scripts used in the publication "The influence of spatial distance and environment on small-scale genetic variability in eelgrass and its application for restoration" in the journal Evolutionary Applications. This publication assessed 10 sampling sites along the Swedish coast with a small spatial scale approach (across 1.5 - 14 km distance) and investigated genomic, phenotypic, and environmental data with the aim of identifying donor materialusing 1,689 Single Nucleotide Polymorphisms (SNPs) derived from 2b-RAD sequencing.

Data in this item includes final filtered vcf files, the bioinformatic pipeline, environmental data, sampling site information, and scripts for the data analysis. Sequence data for this study are available on NCBI in BioProject: PRJNA1043091.

Abstract:

Identifying suitable donor sites is an important component of successful restoration and reduces the likelihood that a restoration action will have negative impacts on surrounding populations. Whether the most suitable donor site has (1) fast- growing phenotypes, (2) high genetic diversity, or (3) harbors alleles that are beneficial for the current or future environment at the restoration site is an ongoing debate in restoration genomics. It is also debated whether one single donor site is the best choice, or if a mixed provenance strategy from sites with different characteristics is preferable. For eelgrass restoration, donor material is typically sourced within a few kilometers. It is therefore also this small spatial scale that needs to be considered when testing which local meadows harbor the most beneficial donor material for a given restoration site. We here assessed micro- habitat differences at 10 eelgrass meadows across 1.5–14 km and genotyped the 10 meadows at 1689 single nucleotide polymorphisms (SNPs). We observed substantial differences in temperature regimes, genetic differentiation, and genetic diversity. We found that even on this small scale, 10% of the overall genetic variation was explained by the local environment of the meadow as well as geographic distance and genetic differentiation. We also identified putative adaptive loci associated with environmental variables and detected differences in growth in common- garden mesocosm experiments simulating ambient summer conditions as well as a marine heatwave with concurrent freshening. We highlight that the variation in environment, genetic diversity, local adaptation, the potential for preadaptation for future conditions, and differences in individual growth can be strong in eelgrass meadows even on the small spatial scale. We suggest a donor registry to take into account these differences and narrow down the pool of potential donor meadows to source the most beneficial combination of donor material for any given restoration site.
Keywords: Genetics not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap